Collective Bargaining Autonomy in a Crisis of Legitimacy? An Analysis of Historical Debates - Hagen Lesch; Helena Bach; Sandra Vogel (Journal of Contextual Economics – Schmollers Jahrbuch, 2022)
In Germany, free collective bargaining was introduced after the Great War in November 1918. Tough, it has constitutional status, we can observe that the state monitors and sometimes steers the collective bargaining process. This can be explained by using the Principal Agent Model as an analytical framework. The state acts like a principal, whereas the social partners behave like agents. Whilst the state leaves the regulation of wages and working conditions to social partners, it expects their loyalty in return. In this sense, collective bargaining autonomy must legitimise itself by being useful. The analysis of historical debates since 1918 shows: If social partners fail to contribute to the economic and social policy goals of the state, the state uses various steering instruments to restore their loyalty. Overall, we can observe some learning processes and path dependence of the institutional setting. Furthermore, the state should keep in mind that future steering of collective bargaining autonomy should strengthen social partners' responsibility.
Keywords: J50; J53; J59; K12; 330; Free Collective Bargaining; Social Partners; Contract Theory; Labour Law